(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the role and significance of the use of innovative pedagogical technologies in the development of the sport of rhythmic gymnastics in the conditions of the New Uzbekistan. The issues of improving the process of training athletes are also covered by the usefmodern educational technologies in physical education and sports training.